Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. X - Capestrano Dionisius, Ignatius; Wahyu Handaru, Agung; Wiradendi Wolor, Christian (CV. Lafadz Jaya, 2023)
The purpose of this research is to determine the effect of compensation and the work environment on the performance of employees of PT X, for the collection of data required in research conducted directly in the PT X working environment. This research using descriptive research with quantitative approach, the method used in this research was the distribution of questionnaires given to 110 respondents, workers at PT X will have a positive influence on the performance of its employees, where if the value of the contribution from the provision of Compensation (X) and the Work Environment (Y) increases, so will the contribution value of Employee Performance (Y), and the ability of the independent variable (X) in explaining the dependent variable (Y) is 24.2%, with the remaining 75.8% explained by other variables not discussed in this study. So it can be concluded that there is a positive influence on compensation and improving the quality of the work environment applied by PT X on the performance of its employees